Pengaruh Piutang Dan Utang Jangka Pendek Terhadap Pendapatan Pada PT. Astra International Tbk - Alwi Pratama Putra Siregar; Nurlaila Nurlaila; Atika Atika (Pusat Riset dan Inovasi Nasional, 2024)
The purpose of this research is to determine the effect of short-term receivables and debt on income at PT. Astra International Tbk. This research shows that there is a discrepancy between theory and financial reports at PT. Astra International Tbk. In 2020 and 2021, income decreased, receivables increased in those years, namely 2020 and 2021, while income decreased, and short-term debt increased in 2018 and 2021, and income also increased. The formulation of the problem in this research is whether short-term receivables and debts have an effect on income at PT. Astra International Tbk. The discussion in this research is related to the field of accounting which discusses financial report analysis. The theory used in this research is regarding company income, namely the company's ability to fulfill its short-term obligations, receivables, namely company claims to other parties whose maturity is less than one year, and short-term debt, namely the company's obligations to other parties which must be paid immediately within a period of time. less than one year. The type of research used in this research is quantitative research. The data source used is secondary data obtained via the website www.idx.co.id. Data processing in this research was carried out using SPSS version 23. Data analysis techniques used descriptive tests, normality tests, linearity tests, classical assumptions, hypothesis testing, and multiple linear regression analysis. The results of this research show that there is a partial influence between the receivables variable and the income variable with a calculated t value of 3.264901 > ttable with a value of 2.026192. Partially, short-term debt has an effect on income with a calculated t value of 15.93768 > t table with a value of 2.026192.